LUSI ARDILA: SEORANG PENGUSAHA HOME INDUSTRI DI GANTIANG TANGAH PADANG KECAMATAN ULAKAN TAPAKIS TAHUN 2016-2022 - Rani Zulhitria; Hendra Naldi (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This study discusses the biography of Lusi Ardila, a home industry entrepreneur from Gantiang Tangah Padang, Kecmatan Ulakan Tapakis. This study aims to determine Lusi Ardila's career journey as a home industry entrepreneur and its impact on the lives of the surrounding community. This research uses historical research methods which are divided into four stages. The first stage is heuristic (collecting data), the second stage is source criticism (testing the authenticity of information), the third stage is interpretation (interpreting data), and the fourth stage is historiography (writing). The results of this study explain that Lusi Ardila's career journey began from being an embroidery employee at an embroidery business in Kampuang Kalapuang for two months until finally successfully establishing her own business at home. Not only succeeded in establishing a business and reviving the family economy. Lusi Ardila's business also has a positive impact on the lives of the surrounding community by creating jobs.